Marketing Communications Across Generations: Insight from Indonesia’s Online Marketplaces - Rachbini, Widarto; Anggraeni, Diana; Badari Burhan, Ahmad; Sovianti, Rina; Rahmawati, Emi (Jurnal The Messenger, 2025)
This study explores the complex dynamics of online consumer behavior in Indonesia's online marketplaces, particularly focusing on how hedonic and utilitarian browsing, alongside electronic word-of-mouth (eWOM), impact e-satisfaction and e-loyalty. Grounded in theoretical frameworks like the Technology Acceptance Model (TAM), Expectancy-Disconfirmation Model (EDM), and Social Influence Theory (SIT), the research investigates the varying behaviors across different age groups—Millennials, Generation X, and Baby Boomers. Using a quantitative approach, data was collected via online surveys targeting active marketplace users. The findings reveal distinct generational responses: Millennials and Generation X exhibit stronger associations between browsing behaviors and positive electronic outcomes, such as e-satisfaction, eWOM, and e-loyalty, compared to Baby Boomers. The study underscores the role of marketing communications in fostering positive consumer experiences, highlighting that tailored, segment-specific strategies are essential for improving brand loyalty. Millennials are more influenced by personalized and engaging content, while Generation X values practicality and reliability, and Baby Boomers prioritize trust and customer service. This research provides empirical insights into how businesses can leverage marketing communications to enhance consumer satisfaction and loyalty. The study also offers practical recommendations for businesses to optimize their strategies in Indonesia’s competitive online marketplace by addressing the unique preferences of different generational cohorts. Future research should investigate additional factors influencing consumer behavior and evaluate the long-term effectiveness of segment-specific marketing approaches.